Sistem informasi hospital-based cancer registry berbasis web - Tarudin Sri Mulatsih, Sigit Priyanta (Berita Kedokteran Masyarakat (BKM), 2006)
Background: Information access from conventional medical record takes time and not fully centralizes for data in Pathology Clinic, Laboratory Clinic and other supporting Unit in Dr. Sardjito Hospital. Whereas in fact the data and information are needed for treatment by physician such as to prove diagnose of patients and to decide appropriate therapy to be taken. Therefore, Physician and provider should take data and information from many units which need times. Objectives: This Research build Information System of Hospital-Based Cancer Registry use web programming include input, output, database and implementation. Method: This research is developing research using system developtment life cycle (SDLC) method. SDLC is done in several steps, System analysis, system design and system implementation. Research design use crossectonal approach which has done in August to December 2005 against medical record paper (conventional) regarding children cancer in Dr. Sardjito Hospital. Result: This information system based on web application. This information system will be used for processing data regarding cancer patient including patient identity and clinical data in supporting data from laboratory, progress note and medical therapy had been taken. Data Output from this system are post hospital treatment, top ten cancer disease both outpatients and inpatients, average of visitor number, cancer patient based on region mapping. Model expressed in Data Flow Diagram so that user can find scope of work and how the system works easily. Input form shows detail fields to accommodate data and information more detail and optimal. Control design focused to security access such as input form, data and information with three different level of user that is ordinary user, administrator and super administrator. Conclusion: This Information System can be use to process a data of patients such as patient identity, social data, laboratory data, and progress note, and treatment data of patients. The output or Information's from this information system are made in Map, line graph, pie graph, and histrogram. Keywords: medical record, hospital-based cancer registry, system development life cycle. posthospital treatment